First evidence of the effectiveness of a field application of RNAi technology in reducing infestation of the mite Varroa destructor in the western honey bee (Apis mellifera) - Francesca Bortolin; Emanuele Rigato; Sergio Perandin; Anna Granato; Laura Zulian; Caterina Millino; Beniamina Pacchioni; Franco Mutinelli; Giuseppe Fusco (Parasites & Vectors)
Abstract Background The mite Varroa destructor is the most serious pest of the western honey bee (Apis mellifera) and a major factor in the global decline of colonies. Traditional control methods, such as chemical pesticides, although quick and temporarily effective, leave residues in hive products, harming bees and operators’ health, while promoting pathogen resistance and spread. As a sustainable alternative, RNA interference (RNAi) technology has shown great potential for honey bee pest control in laboratory assays, but evidence of effectiveness in the field has been lacking. Methods We investigated the efficacy and feasibility of a RNAi treatment to improve bee health under natural beekeeping conditions by integrating a honey bee diet with a mixture of dsRNA targeting V. destructor acetyl-CoA carboxylase, Na+/K+ ATPase and endochitinase genes. Results In treated hives, we observed that the average infestation rate of phoretic Varroa mite was reduced by 33% and 42% relative to control bees fed with sucrose and GFP-dsRNA, respectively. The dsRNA treatment did not affect bee survival, and the beekeepers involved in the project found the method manageable in the apiary and non-intrusive to production activities. Conclusions Our findings demonstrate the feasibility and effectiveness of RNAi technology in reducing Varroa mite infestations under natural rearing conditions. This study supports the potential of RNAi as a promising alternative to chemical pesticides, offering a targeted, efficient and sustainable solution for managing V. destructor in honey bee populations. Graphical Abstract